2006
DOI: 10.1111/j.1365-2486.2006.01199.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐regulated effects of free‐air CO2 enrichment on methane emissions from paddy rice fields

Abstract: Using the free-air CO 2 enrichment (FACE) techniques, we carried out a 3-year monofactorial experiment in temperate paddy rice fields of Japan (1998)(1999)(2000) and a 3-year multifactorial experiment in subtropical paddy rice fields in the Yangtze River delta in China (2001China ( -2003, to investigate the methane (CH 4 ) emissions in response to an elevated atmospheric CO 2 concentration (200 AE 40 mmol mol À1 higher than that in the ambient atmosphere). No significant effect of the elevated CO 2 upon season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 39 publications
2
64
0
2
Order By: Relevance
“…A long-term FACE study of temperate paddy rice fields in Japan showed increases (26-51 %) in CH 4 emissions as a result of long-term CO 2 enrichment (Inubushi et al 2003;Tokida et al 2010). Another FACE study of subtropical paddy rice fields that were subjected to a rice-wheat rotation regime in China showed a significant stimulatory effect (53-188 %) on CH 4 emissions without or with a medium addition rate (1,000 kg C ha -1 ) of wheat straw, but there was no significant effect when the conditions included a high addition rate (2,000 kg C ha -1 ) of wheat straw (Zheng et al 2006). The FACE studies that were simultaneously performed at five sites along a transect of oligotrophic peatland mires in Europe demonstrated no significant CO 2 effects on CH 4 emissions (Silvola et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A long-term FACE study of temperate paddy rice fields in Japan showed increases (26-51 %) in CH 4 emissions as a result of long-term CO 2 enrichment (Inubushi et al 2003;Tokida et al 2010). Another FACE study of subtropical paddy rice fields that were subjected to a rice-wheat rotation regime in China showed a significant stimulatory effect (53-188 %) on CH 4 emissions without or with a medium addition rate (1,000 kg C ha -1 ) of wheat straw, but there was no significant effect when the conditions included a high addition rate (2,000 kg C ha -1 ) of wheat straw (Zheng et al 2006). The FACE studies that were simultaneously performed at five sites along a transect of oligotrophic peatland mires in Europe demonstrated no significant CO 2 effects on CH 4 emissions (Silvola et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This demand will most likely lead to increased CH 4 emissions if no appropriate mitigation strategies are developed and applied. The increasing atmospheric carbon dioxide (CO 2 ) concentration is hypothesized to amplify the level of CH 4 that is released from not only natural (Dacey et al 1994;Hutchin et al 1995) but also managed wetlands, including irrigated rice fields (Inubushi et al 2003;Tokida et al 2010;Zheng et al 2006;Ziska et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been also shown that increased [CO 2 ] can significantly enhance CH 4 emission from rice fields, presumably by increasing the C supply from rice roots to the soil, plant conductance of CH 4 (increased transport to the atmosphere), and other factors (Ziska et al, 1998;Allen et al, 2003;Inubushi et al, 2003;Cheng et al, 2006;Zheng et al, 2006). Therefore, there is strong concern that increasing [CO 2 ] will also stimulate global CH 4 emission from rice fields, creating a positive-feedback effect on global warming.…”
Section: Introductionmentioning
confidence: 99%
“…A positive link between soil inorganic N availability and methanogenic activity is plausible, and CH 4 emission in paddy soils has been positively correlated to levels of soil mineralisable N (e.g. Zheng et al, 2006). However, there may be important differences between these heavily fertilised systems and natural wetlands.…”
Section: Ch 4 Production and Oxidation Potentialmentioning
confidence: 99%